2011
DOI: 10.1103/physrevb.84.054503
|View full text |Cite
|
Sign up to set email alerts
|

Detecting phonon blockade with photons

Abstract: Measuring the quantum dynamics of a mechanical system, when few phonons are involved, remains a challenge. We show that a superconducting microwave resonator linearly coupled to the mechanical mode constitutes a very powerful probe for this scope. This new coupling can be much stronger than the usual radiation pressure interaction by adjusting a gate voltage. We focus on the detection of phonon blockade, showing that it can be observed by measuring the statistics of the light in the cavity. The underlying reas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
109
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(114 citation statements)
references
References 58 publications
(81 reference statements)
2
109
1
Order By: Relevance
“…Such transition can be demonstrated by coupling mechanical resonators to other quantum objects [3], including superconducting qubit circuits [4][5][6][7][8][9][10][11][12][13][14], transmission line resonators [15][16][17][18][19], optical cavities [20][21][22][23], nitrogenvacancy (NV) centers [24][25][26], electron spin [27], and twolevel defects [28,29]. For example, the quantization of mechanical oscillations can be demonstrated by phonon blockade [12], which can be measured by a cavity field [30]. Experiments [31][32][33][34] showed that mechanical resonators can be operated in the quantum regime.…”
Section: Introductionmentioning
confidence: 99%
“…Such transition can be demonstrated by coupling mechanical resonators to other quantum objects [3], including superconducting qubit circuits [4][5][6][7][8][9][10][11][12][13][14], transmission line resonators [15][16][17][18][19], optical cavities [20][21][22][23], nitrogenvacancy (NV) centers [24][25][26], electron spin [27], and twolevel defects [28,29]. For example, the quantization of mechanical oscillations can be demonstrated by phonon blockade [12], which can be measured by a cavity field [30]. Experiments [31][32][33][34] showed that mechanical resonators can be operated in the quantum regime.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, quantum effects were also confirmed in a mechanical drum resonator coupled to a superconducting microwave cavity [2] and in cavity optomechanical systems [3,4]. This breakthrough shifted the interest to the possible use of mechanical systems as quantum state transducers [5,6] and eventually to the construction of integrated coherent mechanical-based circuits. Investigation of fundamental properties of coupled mechanical resonators is essential to achieve this goal.…”
mentioning
confidence: 93%
“…In this situation, we can disregard the last term in Eq. (5). This statement imposes constraints on the ac displacement which can be found from the following inequality, i, j 2A i I n j + A n I i j u i u j i jk I i j I kn u i u j u k , see Ref.…”
mentioning
confidence: 99%
“…Lattice arrays of coupled cavities mimicks the collective behavior of many body coupled systems in quantum phase transitions [9][10][11][12]. Coupled resonator systems of cavities appears as the test bed for photon blockade and localization-delocalization transition in both strong and ultrastrong coupling regimes [13][14][15].…”
Section: Introductionmentioning
confidence: 99%